PENERAPAN PROBLEM BASED LEARNING DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA SEKOLAH DASAR - Theodosia Ndole; Maria Ana (Program Studi Pendidikan Matematika, 2021)
This research was conducted to improve the mathematics learning outcomes of elementary school students by using the Problem Based Learning model. The method used in this research is Classroom Action Research. Class IV SDK Ndona 2 students totalling 16 students are the subjects in this study. The results before the action were taken, namely, in the pre-cycle, only 6 students or 37.5% completed, in the first cycle increased to 10 students or 62.5% who completed learning mathematics and in the second cycle increased again to 14 students who completed learning mathematics or 87, 5%. This study is said to be successful because it achieves performance indicators, namely more than 80% of all students with a minimum standard of more than 70. Based on the results of the study, it can be concluded that learning with the Problem Based Learning model can improve learning outcomes in mathematics students.